Review : Antioxidant in Oral Health - A Recent Scenario - Prabal Pal; Harman; Puneet Sharma; Nitin Verma (Wolters Kluwer Medknow Publications, 2004)
Cancer is a crab like disease where 17.9 million persons of the world are suffering from this disease. In India 16.4/100000 male persons are suffering from Oral Cancer and while for women it is 8.8/100000 person. In urban India Cancer incidence ranges from 106 to 130.4 men/100000, 100 to 140.9/100000 for women. The most important predisposing factors for developing cancer are bidi, chutta smoking, chillum, hookah, betel quid chewing and khaini chewing. Annually about 75000 to 80000 persons develop Oral Cancer (as primary tumor) annually. I have seen that proper supplement of vitamin A, E, C, retenoic acid, selenium, alpha lipoid acid, spirulina, and all the plant antioxidants has tremendous chemopreventive properties to protect the population from Oral Cancer. This article will deals mainly with the protective effect of plant (phytochemicals) and also about flavonoids (obtained from black tea), and theoflavins - as a chemopreventors to Oral Cancer.